2021
DOI: 10.3390/jpm11090882
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Modulate SARS-CoV-2 Viral Load Kinetics: A Longitudinal Analysis of 1735 Subjects

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 represents a public health emergency, which became even more challenging since the detection of highly transmissible variants and strategies against COVID-19 were indistinctly established. We characterized the temporal viral load kinetics in individuals infected by original and variant strains. Naso-oropharyngeal swabs from 33,000 individuals (admitted to the IRCCS Santa Lucia Foundation Drive-in, healthcare professionals and hospitalized patients who underwent routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Prior to the detection of Omicron BA.1, older individuals have been found to take longer to clear infection on average than younger individuals. (Caputo et al, 2021; Cevik et al, 2021; Jones et al, 2021; Long et al, 2021; Néant et al, 2021; Singanayagam et al, 2022) However, these findings are not unequivocal, as a previous systematic review found the effect of age on viral kinetics was diminished after accounting for disease severity. (Chen et al, 2021) Our data support an effect of age on viral clearance times, with longer times from peak to clearance in individuals >50 years compared to those <30 years regardless of lineage and immune state.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the detection of Omicron BA.1, older individuals have been found to take longer to clear infection on average than younger individuals. (Caputo et al, 2021; Cevik et al, 2021; Jones et al, 2021; Long et al, 2021; Néant et al, 2021; Singanayagam et al, 2022) However, these findings are not unequivocal, as a previous systematic review found the effect of age on viral kinetics was diminished after accounting for disease severity. (Chen et al, 2021) Our data support an effect of age on viral clearance times, with longer times from peak to clearance in individuals >50 years compared to those <30 years regardless of lineage and immune state.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of age on viral kinetics complicates the interpretation of these findings. Prior to the detection of Omicron BA.1, older individuals have been found to take longer to clear infection on average than younger individuals ( Caputo et al, 2021 ; Cevik et al, 2021 ; Jones et al, 2021 ; Long et al, 2021 ; Néant et al, 2021 ; Singanayagam et al, 2022 ). However, these findings are not unequivocal, as a previous systematic review found the effect of age on viral kinetics was diminished after accounting for disease severity ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported different results. For example, a study conducted in the USA reported a significantly higher viral load in males 26 , and the same trend was observed in Italy, although it was found that males had a faster viral load decay than females, and the viral load decayed more slowly in older patients 27 . Studies from Australia 28 and Turkey 29 , on the other hand, reported no significant difference in viral loads among patients of different sexes and age groups.…”
Section: Discussionmentioning
confidence: 69%